PERAN ATRIBUT PRODUK DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN WARDAH DI PALU - Hasmawati, Hasmawati (Fakultas Ekonomi Universitas Tadulako, 2020)
The research Sims to determine the rope of Product Attributes and Social media on Purchasing Decisions to buy Wardah Brand Cosmetics In Palu City. This type of research ia casual serearch. The independent variable ia the Product attribute (X1) and Social media (X2), while the dependent variable ia the purchase decision (Y). The collection methods used were questionnaire, literatur study, and interview. The sampling technique used purposive sampling with a sample size of 120 respondents. The data analisys method used multiple linear regression, F test and t test. Product attribute and social media simultaneously have significant effect towards purchasing decisions of Wardah?s Customers in Palu, Product attribute partially has significant effect towards purchasing decision, as well as social media partially has significant effect towards purchasing decision of Wardah?s Customers in Palu.